Collaborative Governance In Household Handling - Sabaruddin, Abdul Sabar; Said, Achmad Lamo (International Journal of Scientific Research and Management (IJSRM), 2018)
This study will examine and analyze collaborative governance processes as the basis for the formation of collaboration and the factors that influence collaborative governance in the handling of uninhabitable house. The research method used is a qualitative approach and the type of research is action research, known as participatory action research (PAR). Basically, PAR is a research that actively involves all relevant parties (stakeholders) in assessing actions or interactions between organizations in order to make changes and improvements in a better direction. Data collection is done by participant observation, interviews, and document search. Data analysis technique is an interactive analysis which includes the stages of data reduction, data presentation and data verification / drawing conclusions.      Moreover, the results of the study, the process of collaborative governance in the handling of uninhabitable houses in Kolaka and North Kolaka Districts was carried out through formal mechanisms and informants, including (1) dialogue between actors: the stage of formal and informal dialogue between actors. Formally, the dialogue  was through a joint forum by forming housing and settlement areas (POKJA PKP). While not formally planning and implementing the handling of uninhabitable houses puts forward deliberation (2) builds consensus: the actors involved have responsibilities that have been decided together. Furthermore, the regional government prepares the budget through the APBD and the Housing and Settlements Agency as the executor and the person in charge of the program. The village / kelurahan government is involved in data collection and verification of uninhabitable houses. The private sector is involved in the supply of building materials and the community participates in the form of willingness to become labor and readiness to provide materials. (3) commitment to goals: this phase describes the recognition of actors involved in collaboration to be responsible for solving public problems. The realization of this commitment is the implementation of the program with a participatory approach. Meanwhile, the factors that influence collaborative governance are: (1) leadership, (2) communication, (3) commitment, and (4) common vision.